2020
DOI: 10.1002/pa.2329
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare expenditure and health outcome nexus: Exploring the evidences from Oman

Abstract: Funding information The Research Council Present study examine the effect of public healthcare expenditure on health outcome in Arab Golf region by using World Bank world development indicators data. This study found that health expenditure had a significant effect in improving health outcome in this region. The effects of health expenditures on infant mortality rate, child mortality rate and maternal mortality rate are negative and statistically significant implying that the public health expenditures is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…on that there is a strong, positive association between total healthcare expenditures and total life expectancy in selected East African Countries, Dhrif 3 on that healthcare expenditure reduces child mortality rates in 93 developed and developing countries, Rahman et al 8 . on that healthcare expenditure is tackling infant mortality in the ASEAN, Ray and Linden 23 on that public health expenditures are generally more health‐promoting than private expenditures in 195 countries, Al‐Azri et al 24 . on that healthcare expenditure has an effect on healthcare outcomes by lowering infant mortality rates, child mortality rates, and maternal mortality rates in the Arab Gulf region, Bein and Coker‐Farrell 25 on that healthcare expenditure has an impact on health status, with public healthcare expenditure having a greater impact than private healthcare expenditure in eight African countries, and Haque et al 26 .…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…on that there is a strong, positive association between total healthcare expenditures and total life expectancy in selected East African Countries, Dhrif 3 on that healthcare expenditure reduces child mortality rates in 93 developed and developing countries, Rahman et al 8 . on that healthcare expenditure is tackling infant mortality in the ASEAN, Ray and Linden 23 on that public health expenditures are generally more health‐promoting than private expenditures in 195 countries, Al‐Azri et al 24 . on that healthcare expenditure has an effect on healthcare outcomes by lowering infant mortality rates, child mortality rates, and maternal mortality rates in the Arab Gulf region, Bein and Coker‐Farrell 25 on that healthcare expenditure has an impact on health status, with public healthcare expenditure having a greater impact than private healthcare expenditure in eight African countries, and Haque et al 26 .…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Secondary education, on the other hand, does not provide the same health benefits as primary education. Al-Azri et al 24 examine the impact of public healthcare expenditure on healthcare outcomes in the Arab Gulf region over a 20-year period using fixed and random effects models. The findings show that healthcare expenditure has an impact on healthcare outcomes by reducing infant, child, and maternal mortality rates; however, it has no effect on non-communicable disease deaths.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that public health spending is typically more health-promoting than private spending. Al-Azri et al (2020) assessed the effect of public healthcare expenditure on health outcomes in Oman using country-level data from the World Bank. The authors found that increasing health expenditure significantly reduces infant mortality rate, child mortality rate and maternal mortality rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings revealed that public health spending is typically more health-promoting than private spending. Al-Azri et al. (2020) assessed the effect of public healthcare expenditure on health outcomes in Oman using country-level data from the World Bank.…”
Section: Literature Reviewmentioning
confidence: 99%